“After School Exercise”: A Program to Promote Students’ Physical Activity II. Students’ Perceptions of the Program (Short version of a Greek article) - Syrmpas, Ιωάννης; Andreadou, Ευαγγελία; Asteriou, Θεανώ; Babani, Ξανθή; Brisimis, Eύαγγελλος; Papavasileiou, Σπύρος; Skourgia, Ελένη; Faltakas, Ευθύμης; Chatzipanteli, Αθανασία; Goudas, Μάριος (Inquiries in Physical Education and Sport, 2020)
The purpose of the present study was to examine fifth and sixth graders’ perceptions of and their experiences with the program entitled “After School Exercise”. Twenty students were purposefully selected and participated in the study (N = 7 boys, N = 13 girls). The students were asked to answer open-ended questions. The results indicated that the students had positive experiences with participating in the program. They also stated that due to their participation in the program they increased the time they spent in physical activity (PA). Finally, different aspects of the program were found to be attractive to them. This confirms that students have different characteristics and needs that curriculum designers should consider when designing a new curriculum. The provision for PA with a differentiated level of difficulty and parents’ involvement in extracurricular PA proved to be effective strategies, based on students’ reports, in promoting their participation in PA.